2014
DOI: 10.1370/afm.1691
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Primary Care Patients to Use a Patient-Centered Personal Health Record

Abstract: PURPOSE Health care leaders encourage clinicians to offer portals that enable patients to access personal health records, but implementation has been a challenge. Although large integrated health systems have promoted use through costly advertising campaigns, other implementation methods are needed for small to medium-sized practices where most patients receive their care. METHODSWe conducted a mixed methods assessment of a proactive implementation strategy for a patient portal (an interactive preventive healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 30 publications
5
75
2
2
Order By: Relevance
“…While this may limit the transferability of the findings to younger, healthier populations, it is important to understand these patients’ perspectives because they may be the early adopters of this technology. The positive views expressed by older patients is consistent with recent literature16 mitigating previous concerns that older people will not be able to make use of portals 17. A study by Kerns et al18 found that patients’ trust in a personal health record was related to its recommendation by their clinician.…”
Section: Discussionsupporting
confidence: 86%
“…While this may limit the transferability of the findings to younger, healthier populations, it is important to understand these patients’ perspectives because they may be the early adopters of this technology. The positive views expressed by older patients is consistent with recent literature16 mitigating previous concerns that older people will not be able to make use of portals 17. A study by Kerns et al18 found that patients’ trust in a personal health record was related to its recommendation by their clinician.…”
Section: Discussionsupporting
confidence: 86%
“…As seen in other studies,17 the baseline registration rate for patient portals at our academic institution was high (50%). However, our study obtained more detailed data to determine which features of our portal are actually being used.…”
Section: Discussionsupporting
confidence: 82%
“…Researchers have used the mixed methods approach to examine nuanced topics, such as electronic personal health records, 3 knowledge resources, 4 patientphysician communication, 5 and insight about intervention feasibility and implementation practices. 6 Mixed methods research is the collection and analysis of both qualitative and quantitative data and its integration, drawing on the strengths of both approaches.…”
Section: Introductionmentioning
confidence: 99%